Donut Che Nah / Nur Zakiah Husna Zamzuri Akmar - Zamzuri Akmar, Nur Zakiah Husna (Universiti Teknologi MARA, Kedah, 2025)
Donut Che Nah is a unique brand inspired by the name of its original owner, Nurul Farhanah, and has successfully attracted the attention of sweet food enthusiasts in Malaysia because Donut Che Noh has become the first producer of milk donuts. With its soft and sweet taste, this donut has received a warm welcome from customers since its introduction.Donut Che Noh comes with several attractive and appetizing decoration variations, including chocolateflavored milk donuts with decoration options such as original, nuts, and chocolate sprinkles. This variety allows customers to choose according to their taste, making the brand increasingly popular among donut enthusiasts. The original recipe for this donut was actually adapted by Nurul Farhanah's mother-in-law, who hails from the state of Sarawak. Social media platforms have helped expand the brand's reach, with satisfied customers sharing their experiences and enticing pictures of the donuts online. This has made Donut Che Noh a popular name not only in the local area but also in other parts of Malaysia.In conclusion, Donut Che Noh is not just an ordinary donut brand, but it carries a deeper meaning through its story. The name, taken as a tribute to the original shop owner, the use of traditional recipes perfected by the mother-in-law, and the various decoration options make this brand unique and full of sentimental value. This milk donut not only created a phenomenon as the first of its kind in Malaysia but also solidified the brand's position as the top choice for customers. With a wise approach in combining tradition and innovation, Donut Che Noh has firmly established itself as a beloved and influential name in the Malaysian food scene.